Arsenic Concentration in Wild Plants Growing on Two Mine Tailings - Carmen Angeles, Ma del; Chávez, González-; Scheherazada, Ariadna; López, Sánchez-; Carrillo-González, Rogelio (Pharmacognosy Communications)
Introduction: Plant metalloid contamination may represent an important pathway of Arsenic (As) intake by humans, wild herbivores and livestock. Objective: This study aimed at estimating Arsenic (As) exposition risks to wild plants naturally growing on the contaminated area of Zimapan, Hidalgo, Mexico. Materials and Methods: Arsenic concentrations in the rhizosphere, aerial and root parts, and deposition on leaves of wild plants from two mine tailings were analyzed. Results: The range of total and EDTA-extractable Arsenic (As) concentrations on the mine tailings were from 4016 to17,178 mg kg-1 and from 234 to 499 mg kg-1, respectively. Eleven plant species were the dominant vegetation. Some of these are important in the folk Mexican medicine. Retention of Arsenic (As) in aerial part was between 49 to 7,521 mg kg-1. The highest shoot As concentration, bioconcentration and translocation factors were observed in Gnaphalium. (2,939 mg kg-1, 5.7, 10.3) and Aster gymnocephalus leaves (2,409 mg kg-1, 8.6 and 9.6, respectively). Juniperus sp and Ruta graveolens behaved As excluders, while Dalea bicolor accumulated Arsenic (As) close to the maximum tolerate concentrations to animals. After a very drastic washing procedure, leaves still had structural high Arsenic (As) concentration (49-2, 940 mg kg-1). Conclusion: This study highlighted that plants are important organism for retaining Arsenic (As) not only on leaves surface but also structurally. Therefore, they strongly influence Arsenic (As) dispersion and risk from mine tailings. Phytoremediation using some of these plants is suggested taking into account control measures to deplete Arsenic (As) transfer to livestock or medicinal herb use.
Keywords: Food web; Hyperaccumulation; Metalloid transfer; Native plants; Phytoremediation; Plant accumulation